Identify korean pop market segmentation in west java - Eka M, Trishanty; Fachira, Ira (Journal of Business and Management, 2019)
Korean Wave has invaded several Asian countries including Japan, China, Thailand, and also Indonesia. Korean Wave that also known as Hallyu / ?? / ?? is stand for the spread of South Korean Culture such as Music or Korean pop (K-POP), Korean drama (K-drama), Movie (K-movie), and so on. In Indonesia, Korean Wave can be seen from many Korean brand cosmetic, Korean Drama on local TV program, Korean Culture Event held by local organizer and also many Korean boy band and girl band Concert held in Indonesia. This is opportunity for marketers to seek information and be in the market. This paper will focus on identifying Korean Pop Fans demographic, behavioral and customer physiographic that influence them toward choosing and buying specific K-POP products using segmentation method. This 6-month study will focus on identifying Korean Pop Fans profile segmentation base on their demographic such as gender, age, educational, occupation, income, type of product and willingness to pay; geographic such as region; behavior such as user status, buyer readiness stage, loyalty status; and physiographic such as activity, interest, opinion, value and lifestyle using two step cluster. The optimal number of clusters in this research is two, which are then labeled as one fandom and multi fandom based on their rate. However, multi fandom shows more effective because this cluster willing to pay more to satisfy their hearts. Keywords : Customer behavior, Korean pop, Korean Wave, Segmentation